2009
DOI: 10.1163/156853809787392676
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase A2 activity of crocodile serum

Abstract: The catalytic activity of phospholipase A 2 (PLA 2 ) was measured in serum samples from 32 crocodiles in Thailand and Australia by a method using 14 C-oleic acid-labelled autoclaved Escherichia coli membranes as a substrate. The highest PLA 2 activity was measured in the serum of Crocodylus siamensis (n = 9, mean ± SD), 13.3 ± 3.1 U/l followed by hybrid C. siamensis × C. porosus (n = 6), 10.4 ± 8.7 U/l and Crocodylus porosus (n = 17), 4.3 ± 3.0 U/l. The difference between C. siamensis and C. porosus was highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…More recently, circulating PLA2 has been identified in a variety of crocodilian species. Nevalainen et al [18] detected PLA2 in the serum of both saltwater (Crocodylus porosus) and Siamese crocodiles (C. siamensis) using radiolabeled fatty…”
Section: Resultsmentioning
confidence: 99%
“…More recently, circulating PLA2 has been identified in a variety of crocodilian species. Nevalainen et al [18] detected PLA2 in the serum of both saltwater (Crocodylus porosus) and Siamese crocodiles (C. siamensis) using radiolabeled fatty…”
Section: Resultsmentioning
confidence: 99%
“…PLA 2 has been identified in reptiles, but primarily in snake (reviewed in Fraenkel-Conrat, '82) and lizard (Fry et al, 2005) venoms. However, recently Nevalainen et al (2008) showed that PLA 2 enzyme activity could be detected in both Siamese (Crocodylus siamensis) and saltwater (Crocodylus porosus) crocodiles. This study employed radiolabeled fatty acids to probe PLA 2 activities in crocodiles.…”
Section: Discussionmentioning
confidence: 99%
“…The physical barriers, such as the skin and gut mucosa, prevent the entry of pathogens, whereas chemokines refer to a category of small proteins involved in cell signalling. The documented cytokines in crocodilians include lysozymes, phospholipase A2 (PLA2), antimicrobial peptides (AMPs) (defensins and cathelicidin), complement proteins, and dipeptidyl peptidase IV (DPP4) 20,29,31,57,59‐61 …”
Section: The Immunity Of Crocodilesmentioning
confidence: 99%
“…The organs of crocodiles, including the bile, liver, lung, gall bladder, heart, lungs, intestine, and brain, have been suggested to have antimicrobial and antitumour effects 16‐19 . As a primary transport medium supporting all the body parts, it is believed that crocodile blood holds the key for the maintenance of health and metabolic balance, leading to a lot of studies on its effects on microbial infection, 16,20‐36 viral infection, 37 inflammation, 26,38‐44 oxidation, 25,27,38,39,41,43‐47 tumors, 16,23,48‐55 wound healing, 22,25 and iron‐deficiency anaemia 56…”
Section: Introductionmentioning
confidence: 99%